PELIPUTAN INVESTIGASI, PROFESIONALISME WARTAWAN INVESTIGASI DAN INTERPLAY ANTARA STRUKTUR DAN AGENCY (Studi Kasus Dalam Praktiknya di majalah Tempo) - Johny Herfan (BPSDMP Kominfo Jakarta, 2015)
ABSTRACTBackground of this study is the phenomenon of investigative reporting practice in relation to the journalist’s professionalism. This research method is the case study. This research focuses oninvestigative reporting practice in Tempo magazine; journalist’s professionalism in investigating in perspective of competency standards of reporter; and interplay between structure and agency. The conclusion is journalist have competency to conduct investigative reporting on the basis of good experience. In the implementation of journalist-competency standard, detail process of investigation can not be conducted according to working procedure. The fact shows that investigative reporting ofTempo is earlier in situation anticipation. In the process of investigative reporting,the role of structure and agency gives freedom to each other for journalists. Investigation team’s rule of Tempo enables and constrains according to rule and resources. But, Tempo investigative reporting team has its own standards. In certain cases of investigative reporting, Tempo reporters implement higher level of competency than journalist-competency standard. Related to Structuration theory between structure and agency structure in reality, structure do not overburden team performance.The structure does not hold a decisive role. Interplay does not depend on structure. Other researchers should conduct observation research in media which apply competency test for reporters from other agencies. Keywords: Investigative Coverage; Professionalism of InvestigatingJournalist; Interplay; Structure; Agency. ABSTRAKBerlatarbelakangkan fenomena praktik liputan investigasi dalam kaitan profesionalisme wartawan, penelitian bermetode studi kasus ini fokus pada soal : praktik peliputaninvestigasi di majalah Tempo; profesionalisme wartawan investigasi dalam perspektif Standar Kompetensi Wartawan di Majalah Tempo; dan interplay antara struktur dan agency dalam praktik peliputan investigasi di majalah Tempo. Penelitian menyimpulkan : Wartawan berkompeten dalam SKW melakukan peliputan investigasi berdasarkan pengalaman yang mumpuni. Di dalam penerapan SKW, rincian teknis proses kerja investigasi tidak dapat dilakukan oleh wartawan berkompeten sesuai dengan urutan langkah kerja. Kenyataan di lapangan menunjukkan tim peliputan investigasi Tempo lebih dini mengantisipasi situasi. Dalam proses organisasi liputan investigasi, perananstruktur dan agensi saling memberi keleluasaan bagi wartawan. Aturan yang dimiliki tim investigasi Tempo memberi enabling dan constraining, sesuai dengan rule dan resources. Akan tetapi, tim liputan investigasi Tempo memiliki tolok ukur tersendiri. Dalam kasus peliputan investigasi tertentubahkan tim investigasi Tempo menerapkan standar kompetensi wartawan yang lebih tinggi materi peliputannya daripada SKW. Terkait Teori Strukturasi antara struktur dan agency ternyata struktur pada investigasi Tempo tidak terlalu membebani kinerja tim. Struktur tidak memegang peranan yang menentukan. Interplay tidak tergantung dari tujuan struktur. Para peneliti lain perlu melakukan penelitian observasi di media yang mengikuti uji kompetensi wartawan dari lembaga lain.Kata-kata Kunci : Peliputan Investigasi; Profesionalisme Wartawan Investigasi; Interplay; Struktur ; Agency.